Descending Influences on Vestibulospinal and Vestibulosympathetic Reflexes - McCall, Andrew A.; Miller, Derek M.; Yates, Bill J. (Frontiers in Neurology, 2017)
This review considers the integration of vestibular and other signals by the central nervous system pathways that participate in balance control and blood pressure regulation, with an emphasis on how this integration may modify posture-related responses in accordance with behavioral context. Two pathways convey vestibular signals to limb motoneurons: the lateral vestibulospinal tract and reticulospinal projections. Both pathways receive direct inputs from the cerebral cortex and cerebellum, and also integrate vestibular, spinal and other inputs. Decerebration in animals or strokes that interrupt corticobulbar projections in humans alter the gain of vestibulospinal reflexes and the responses of vestibular nucleus neurons to particular stimuli. This evidence shows that supratentorial regions modify the activity of the vestibular system, but the functional importance of descending influences on vestibulospinal reflexes acting on the limbs is currently unknown. It is often overlooked that the vestibulospinal and reticulospinal systems mainly terminate on spinal interneurons, and not directly on motoneurons, yet little is known about the transformation of vestibular signals that occurs in the spinal cord. Unexpected changes in body position that elicit vestibulospinal reflexes can also produce vestibulosympathetic responses that serve to maintain stable blood pressure. Vestibulosympathetic reflexes are mediated, at least in part, through a specialized group of reticulospinal neurons in the rostral ventrolateral medulla (RVLM) that project to sympathetic preganglionic neurons in the spinal cord. However, other pathways may also contribute to these responses, including those that dually participate in motor control and regulation of sympathetic nervous system activity. Vestibulosympathetic reflexes differ in conscious and decerebrate animals, indicating that supratentorial regions alter these responses. However, as with vestibular reflexes acting on the limbs, little is known about the physiological significance of descending control of vestibulosympathetic pathways.